Nepal Development Update, September 2016 : Powering Recovery - World Bank (World Bank, Washington, DC, 2016)
After registering the weakest growth in 14 years during FY2016, economic activity is recovering in Nepal. Agriculture and construction are expected to improve on the account of a good monsoon as well as increased disbursements of housing reconstruction grants. Coupled with in-creased government spending, this is expected to push FY2017 growth to 5 percent and to remain in line with potential thereafter. This edition of the Nepal Development Update examines the key economic developments in Nepal over the preceding months, placing them in a longer term and global perspective. In the Special Focus section, the authors take a closer look at what it would take for the electricity sector to power Nepal’s recovery. Over the past decade, power outages in Nepal have increased substantially. Availability of reliable and affordable electricity has become a major constraint for Nepal’s development as it hampers the ability to improve living standards, raise agricultural productivity and income, and help youth transition from farming to non-farm employment through creation of new industries at home. Given Nepal’s natural endowments, it is not difficult to envision an electricity sector that can support green growth, poverty reduction, and shared prosperity. Such an electricity sector would not only meet domestic demand reliably, affordably, and cleanly, but would earn revenue from export of surplus hydropower through enhanced regional electricity markets to neighboring countries by integrating the wider South Asia power market. Wholesale structural reforms of the electricity sector are needed to achieve this.